2010
DOI: 10.1116/1.3456123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sputter rates of oxide films relative to the sputter rate of SiO2

Abstract: New method of calculating adsorption and scattering for Xe-Pt (111) using Direct Simulation Monte Carlo techniques J. Vac. Sci. Technol. A 30, 061401 (2012) Current-voltage-time characteristics of the reactive Ar/O2 high power impulse magnetron sputtering discharge J. Vac. Sci. Technol. A 30, 050601 (2012) Influence of magnetic ordering on the elastic properties of PdFe3N J. Vac. Sci. Technol. A 30, 030602 (2012) Investigation of the factors determining the SIMS depth resolution in silicon-isotope multiple lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…The film thickness was estimated using the depth at which the oxygen intensity reached half of the maximum, as used by several authors [2,21,22]. It is important to consider that the etch rates of Fe-and Cr-oxides differ from those of SiO 2 as reported for one example by Baer [23]. Because the surface films consist of mixed oxides and hydroxides of Fe, Cr and Mo, it is very difficult to exactly estimate the real sputter rates.…”
Section: Xps Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The film thickness was estimated using the depth at which the oxygen intensity reached half of the maximum, as used by several authors [2,21,22]. It is important to consider that the etch rates of Fe-and Cr-oxides differ from those of SiO 2 as reported for one example by Baer [23]. Because the surface films consist of mixed oxides and hydroxides of Fe, Cr and Mo, it is very difficult to exactly estimate the real sputter rates.…”
Section: Xps Analysismentioning
confidence: 99%
“…First, it is reported in literature that the etch rates of Cr-and Fe-oxides are lower than SiO 2 [23,30], causing in principle an overestimation of the XPS oxide growth from sputter profiles. Secondly, the calculated oxide thickness based on the electrochemical data bears small inaccuracies as the total dissolution current density does not account for dissolution of B and C. The contribution of C to the resulting current is expected to be very low.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…However, it has been shown that most metal oxides sputter slower than SiO 2 (1.6 nm/min), by percents not exceeding $50%. 21 It should also be noted that the sensitivity factors of erbium-based materials are not well established. Therefore, the AES data was converted to relative atomic composition versus depth by applying the relative sensitivity factors derived empirically from elemental standards.…”
Section: B Elemental Composition and Phase Formationmentioning
confidence: 99%
“…XPS allows identifying the elemental distribution on the surface, and also detects the individual chemical states of each element. Additionally, during the sputtering process, the oxide layer penetration time can be measured and the layer thickness can be predicted by using calibration data and standard equations [23]. A scanning-electron microscope (SEM-LEO Gemini 1530 with a ThermoNORAN Vantage X-ray analyzing system manufactured by Thermo Scientific) was used to identify the changes in surface morphology and average composition of the corroded material.…”
Section: Methodsmentioning
confidence: 99%